Committed teams : three steps to inspiring passion and performance - Moussa, Mario; Boyer, Madeline, 1987-; Newberry, Derek, 1983- (Wiley, 2016)
"Build high-performing teams with an evidence-based framework that delivers results Committed is a practical handbook for building great teams. Based on research from Wharton's Executive Development Program (EDP), this concise guide identifies the common challenges that arise when people work together as a group and provides key guidance on breaking through the barriers to peak performance. Committed draws its insights from the EDP's living lab: an intensive two-week simulation during which executive-level participants run complex global businesses. The authors have observed over 100 teams collaborating and competing for over 100 combined years in this intense environment. It has yielded fundamental insights about teamwork: what usually goes wrong, what frequently goes right, and the methods and techniques that will help you access your team's full potential. These insights have been distilled into a simple, repeatable process that you can start applying today. Getting teams engaged and aligned is hard. Committed will give you the tools you need to deal with all of the familiar teamwork challenges that get in the way: organizational politics, delegation, coordination, and aligning skills and motivation. Using vivid stories and examples from the worlds of business, sports, and non-profits, it will teach you how to: Understand the dynamics of successful teams Achieve peak performance using a research-backed methodology Gain expert insight into why most teams underperform Learn the critical points common to all great teams Committed gives you the perspective you need to combine the right people with the right way of collaborating to achieve extraordinary results"--